The Onset of Action of the Presumption of Innocence Principle - Igor Y. Murashkin (Сибирское юридическое обозрение, 2016)
The author explores the problematic issues of the beginning of the principle of presumption of innocence. Critically evaluate the currently existing position of the origin of the right to protection against unjustified allegations guilty to the crime since the initiation of criminal proceedings. Grounded approach to the beginning of this principle since, when in fact it became prosecute.